The Effect of the CBT Counseling Approach to Overcoming Academic Procrastination: A Systematic Literature Review - Suminarni, Nanik; Wahyuni, Fitri; Ramli, M. (Yayasan Minang Darussalam, 2025)
Academic procrastination is a behavior of delaying academic tasks that leads to a lack of optimization of individual academic performance and also causes negative impacts on individual psychology. Guidance and Counseling services can apply certain approaches or techniques to overcome academic procrastination. One of them is CBT counseling approach that targets changes in the irrational mindset of procrastinators and improves their behavior. Through SLR, this study examines the effect of CBT counseling approach in reducing academic procrastination behavior. The national article search used the Google Scholar database with a publication period between 2020 and 2024 and found 9 articles. Based on the review of these articles, it was concluded that CBT counseling approach is able to reduce academic procrastination behavior.